KH. Ihsan Jampes sebagai Ulama Nusantara: Analisis Pemikiran Fikih tentang Kopi dan Rokok dalam Irsyād al-Ikhwān - Sirojudin (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The book "Irshad al-Ikhwān li Bayān Syurb al-Qahwah wa al-Dukhān" by K.H. Ihsan Jampes of Kediri is an important work in the treasury of Islamic scholarship, examining issues of Islamic jurisprudence and socio-religious ethics contextually. This book was written in response to prevailing social practices, particularly the habit of consuming coffee and cigarettes, which gave rise to differing legal views among scholars. Through an argumentative approach based on naqli and aqli evidence, K.H. Ihsan not only outlines legal classifications—such as halal (permissible), haram (forbidden), makruh (rejected), and mubah (permissible)—but also emphasizes considerations of benefits and harms for individuals and society. The book's uniqueness lies in its discussion, which is not merely legalistic but also includes explanations of the wisdom, ethical impact, and spiritual dimensions of an action. Thus, "Irshad al-Ikhwān" serves not only as a legal reference but also as a means of fostering the moral and spiritual awareness of the community. This study aims to examine the background, characteristics of thought, and significance of the book Irshād al-Ikhwān in enriching the discourse of moderate, contextual, and relevant Islamic jurisprudence (fiqh) to the social dynamics of society. Keywords: Irshād al-Ikhwān, K.H. Ihsan Jampes, social jurisprudence, coffee and cigarettes, religious ethics. AbstrakKitab Irsyād al-Ikhwān li Bayān Syurb al-Qahwah wa al-Dukhān karya K.H. Ihsan Jampes Kediri merupakan salah satu karya penting dalam khazanah keilmuan Islam yang mengkaji persoalan fikih dan etika sosial keagamaan secara kontekstual. Kitab ini disusun sebagai respons atas praktik sosial yang berkembang di masyarakat, khususnya kebiasaan mengonsumsi kopi dan rokok, yang memunculkan perbedaan pandangan hukum di kalangan ulama. Melalui pendekatan argumentatif berbasis dalil naqli dan aqli, K.H. Ihsan tidak hanya memaparkan klasifikasi hukum—seperti halal, haram, makruh, dan mubah—tetapi juga menekankan pertimbangan maslahat dan mafsadat bagi individu dan masyarakat. Keistimewaan kitab ini terletak pada corak pembahasannya yang tidak semata-mata legalistik, melainkan disertai penjelasan hikmah, dampak etis, serta dimensi spiritual dari suatu perbuatan. Dengan demikian, Irshād al-Ikhwān tidak hanya berfungsi sebagai rujukan hukum, tetapi juga sebagai sarana pembinaan kesadaran moral dan spiritual umat. Kajian ini bertujuan untuk menelaah latar belakang penulisan, karakteristik pemikiran, serta signifikansi kitab Irshād al-Ikhwān dalam memperkaya wacana fikih yang moderat, kontekstual, dan relevan dengan dinamika sosial masyarakat. Kata kunci: Irshād al-Ikhwān, K.H. Ihsan Jampes, fikih sosial, kopi dan rokok, etika keagamaan.